Adsorption of thiophene, dibenzothiophene, and 4,6-dimethyl dibenzothiophene on activated carbons - Zhijun Li; Shuangling Jin; Rui Zhang; Xia Shao; Shimin Zhang; Ning Jiang; Minglin Jin; Tingting Meng; Yanhan Mu (Adsorption Science & Technology)
Four activated carbons (ACs) activated by different activation methods from different precursors were heat-treated at 600℃ to decrease surface oxygen functional groups and to separate the effect of pore texture from surface chemistry on their sulfur adsorption performance. The ACs and the heat-treated ones were used as adsorbents for thiophene (T), dibenzothiophene (DBT), and 4,6-dimethyl dibenzothiophene (4,6-DMDBT) for model fuels with or without a competing benzene. The correlations of surface functional groups and pore textures to their adsorption capacities for T, DBT and 4,6-DMDBT were investigated. Results indicated that the heat treatment not only decreased surface oxygen content, but also caused a pore texture modification. The adsorption isotherms can be well fitted by the Langmuir–Freundlich single solute isotherm. The sulfur adsorption capacity of ACs after the treatment for T, DBT, and 4,6-DMDBT has a good linear relationship with the pore volume of pores within 0.536–1.090, 0.536–1.179, and 0.679–1.268 nm, respectively. The decreased percentage of surface oxygen of ACs by the heat treatment is correlated linearly with the decreased percentage of the sulfur adsorption capacity for all the thiophenic compounds. Micropore filling via the π–π interaction is the dominant adsorption mechanism of thiophenic compounds for both the untreated and heat-treated ACs. Surface oxides contribute to the thiophenic adsorption by a cooperative interaction of the π–π interaction and the acid–base interaction between the basic sulfur atom and the acidic carbon atoms linked with oxygen in graphene edges. A flat adsorption is the most possible geometry in the adsorption of thiophenic compounds.